Diplomasi Budaya Seni Reak Juarta Putra Melalui Festival Roskilde di Denmark Pada Tahun (2022) - Fattah, Raihan Abdul; D, Dina (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study discusses the cultural diplomacy undertaken by the arts group Reak Juarta Putra through their participation in the Roskilde Festival in Denmark in 2022. Cultural diplomacy is one of the strategies in international relations to introduce and preserve a country’s cultural heritage. Reak art, as a distinctive traditional art of West Java, is experiencing challenges in the face of globalization and modernization that could potentially erode local cultural values. Reak Juarta Putra’s participation in the Roskilde Festival was a significant effort in promoting Indonesian culture on the international stage as well as strengthening cultural relations between Indonesia and Denmark. The study used a qualitative approach with a descriptive method. Data were collected through interviews with members of the Reak Juarta Putra group, documentation from various sources, as well as analysis on the impact of their participation in the festival. The study also uncovered several barriers faced by the Reak Juarta Putra in conducting their cultural diplomacy, including funding constraints, administrative constraints in the management of travel documents, as well as challenges in presenting authentic elements of Reak art abroad. Specifically, this study highlights how Reak art serves not only as a tool of entertainment but also as a means of constructing national cultural identities at a global level. The Roskilde Festival serves as a strategic platform for Indonesia in promoting its traditional culture and creating closer cultural ties with the international community. Although the challenges faced were considerable, participation in the festival provided valuable insights regarding strategies that could be used to improve the effectiveness of cultural diplomacy in the future. Efforts such as increasing support from the government, strengthening the capacity of arts groups in the face of international challenges, as well as optimizing social media as a promotional tool can be solutions in safeguarding the sustainability of Indonesia’s cultural diplomacy.